Analisis Semiotika Dalam Film Animasi The Anthem Of The Heart - Yulia, Novi; Hasmawati, Fifi; Muslimin (Pubmedia Social Sciences and Humanities, 2024)
This research is entitled "Semiotic Analysis in the Animated Film The Anthem of the Hear". The aim of this research is to determine the meaning of denotation, connotation and myth in the animated film The Anthem Of The Heart. Researchers use descriptive qualitative methods by recording, analyzing, describing the meanings contained in animated films using Roland Barthes' theory of semiotic analysis, namely by analyzing the meaning of denotation, connotation and myth. The data sources used in this research are primary and secondary data. Data collection techniques were carried out by documenting and watching the animated film The Anthem Of The Heart. The research results show that Roland Barthes's semiotics is interesting to use in analyzing a film and has a clear meaning that can be seen from every scene that the researcher analyzes regarding the meaning of denotation, connotation and myth in the animated film The Anthem Of The Heart. The meaning of denotation is a sign that is visible to the five senses, such as images of palaces and outstretched hands, then the meaning of connotation requires a deeper understanding of the meaning of denotation where the meaning of connotation can give rise to various meanings depending on the point of view of the person giving the meaning. The meaning of myth is formed from the meaning of denotation and connotation. According to Barthes, myth is not always related to culture or customs but is also related to ideology that spreads in wider society. It can be seen in the nine scenes that researchers analyzed, such as myths about crying, helping hands, and divorce.